Performance Improvement for Medical Image Transmission Systems using Turbo-Trellis Coded Modulation (TTCM) - Fayssal, M.; Sofiane, B. M.; Mahdjoub, Z.; Lahcene, M. R.; Zerroug, A. (Engineering, Technology & Applied Science Research, 2021)
Digital images have become an essential working tool in several areas such as the medical field, the satellite and astronomical field, film production, etc. The efficiency of a transmission system to exchange digital images is crucial to allow better and accurate reception. Generally, transmitted images are infected with noise. In the medical field, this noise makes the process of diagnosing difficult. To eliminate the transmission errors, an Error Correcting Code (ECC) can be used with the aim to guarantee excellent reception of the images and allowing a good diagnosis. In this paper, source and channel encoding/ decoding functions are studied during medical image transmission (LUNG). At first, the Turbo-Code (TC) is used as ECC and subsequently the Turbo-Trellis Coded Modulation (TTCM). The simulation results represent the curves giving the Bit Error Rate (BER) as a function of the signal to noise ratio (Eb/N0). In order to compare these two systems properly, the MSSIM (Mean Structural Similarity) parameter was used. The obtained results showed the effect and importance of ECC on the transmission of medical images using TTCM which gave better results compared to TC with regard to increasing the performance of the transmission system by eliminating transmission noise.